Pyogenic Granuloma/Peripheral Giant-Cell Granuloma Associated with Implants. (1st December 2015) - Jané-Salas, Enric; Albuquerque, Rui; Font-Muñoz, Aura; González-Navarro, Beatríz; Estrugo Devesa, Albert; López-López, Jose
Abstract : Introduction . Pyogenic granuloma (PG) and peripheral giant-cell granuloma (PGCG) are two of the most common inflammatory lesions associated with implants; however, there is no established pathway for treatment of these conditions. This paper aims to illustrate the successful treatment of PG and PGCG and also report a systematic review of the literature regarding the various treatments proposed. Methods . To collect relevant information about previous treatments for PG and PGCG involving implants we carried out electronic searches of publications with the key words "granuloma", "oral", and "implants" from the last 15 years on the databases Pubmed, National Library of Medicine's Medline, Scielo, Scopus, and Cochrane Library. Results . From the electronic search 16 case reports were found showing excision and curettage as the main successful treatment. As no clinical trials or observational studies were identified the authors agreed to present results from a review perspective. Conclusion . This is the largest analysis of PG and PGCG associated with implants published to date. Our review would suggest that PGCG associated with implants appears to have a more aggressive nature; however the level of evidence is very limited. Further cohort studies with representative sample sizes and standard outcome measures are necessary for better understanding of these conditions.